PERANAN PELATIHAN DALAM PENINGKATAN KINERJA KARYAWAN (Studi Kasus Bagian Operasional PT PLN (PERSERO) Pembangkitan Sumatera Selatan Bagian Selatan) - Elisa Elisa; M.Riska Maulana Effendi; Nur Intan Sari (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This research to know the Role of training to improvement of the employees performance (case study at operational division at PT PLN (Persero) Pembangkitan Sumatera Bagian Selatan with the research problem how is the role of training through the improvement  of the employees performance at operational division at PT PLN (Persero) Pembangkitan Sumatera Bagian Selatan.   The writer used primary data that were collected from the result of intervew to the HRD Manager, and shared the questionnaries to 23 employees which already got the training at operational division and secondary data that were collected from literature like books, journal and the official website of PT PLN (Persero).  The data analyzed by  using qualitative descriptive and quantitative technique with the calculation of the questionnaries result were using percentage formula.  Writer found that the training program in operational division at PT PLN (Persero) Pembangkitan Sumatera Bagian Selatan was good and in accordance with the requirements of the employees and improvement of the employees performance, and after joined the training the employees could increase their team work.  So the training program was very important in the improvement of the employees performance.  Writer suggests PT PLN (Persero) Pembangkitan Sumatera bagian Selatan especially in operational division to keep the traning program because it is very important to the improvement of the employees performance that can impact the qualityof human resources for the improvement of the company and PT PLN (Persero) also should concern to the material and facility that were provided because there were a few employees that still disagree with that.